Antibacterial and anti-biofilm formation activities of high heat tolerant herbal extracts against white feces syndrome-associated Vibrio parahaemolyticus - Bunserm, O.; Choonut, A.; U-taynapun, K.; Chirapongsatonkul, N. (International Journal of Agricultural Technology, 2022)
White feces syndrome (WFS), one of Vibrio parahaemolyticus outbreaks responsible for 10 to 15% loss in shrimp production, has recently been reported. To reduce the losses from WFS, farmers are forced to use expensive antibiotics or probiotics. Several herbal extracts effectively working out in the prevention and control of WFS have also been recorded. However, heat or improper store may cause a deterioration of the herbal extract efficacy. High heat tolerant herbal (HHTH) extracts were therefore focused in this study. Six ethanolic herbal extracts, originated from Caesalpinia sappan, Pluchea indica, Cinnamomum cassia, Alpinia galanga, Ocimum gratissimum, and Origanum vulgare, were screened for their antibacterial activities by disc diffusion method in the forms of heat-treated (heating at 121oC for 15 min) and nonheated. Two of six, C. sappan and A. galanga could be served as the potent HHTH extract. The highest inhibitory activity expressing substance, the HHTH extract of C. sappan, was selected to further determine for its antibacterial and anti-biofilm activities. The minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) against WFS-associated V. parahaemolyticus was the same value of 0.39 mg/ml. Treatment of the test V. parahaemolyticus with the HHTH extract of C. sappan at MIC showed 79.48±1.11% of the biofilm formation inhibition. Scanning electron microscope (SEM) images revealed that no biofilm formation in V. parahaemolyticus treated with the HHTH extract of C. sappan compared to the control. This study elucidated that the HHTH extract of C. sappan could be served as the potential antibacterial and anti-biofilm agent against WFS-associated V. parahaemolyticus which may be used as an alternative natural substance for bacterial control in sustainable aquaculture.